2023
DOI: 10.1002/ptr.7934
|View full text |Cite
|
Sign up to set email alerts
|

Chelerythrine chloride inhibits the progression of colorectal cancer by targeting cancer‐associated fibroblasts through intervention with WNT10B/β‐catenin and TGFβ2/Smad2/3 axis

Abstract: Chelerythrine chloride (CHE) is a benzodiazepine alkaloid derived from natural herbs with significant anti‐tumor and anti‐inflammatory activities. However, the exact role and underlying mechanisms of CHE in colorectal cancer (CRC) remain unclear. Therefore, this study is aimed to investigate the influence of CHE on the progression of CRC. Cell Counting Kit‐8 assay (CCK‐8), transwell, apoptosis rate, cell cycle distribution, reactive oxygen species (ROS), and colony formation determined the anti‐proliferative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…endoplasmic reticulum stress and subsequent apoptosis [15]. Furthermore, research in zebrafish has unveiled that CHE's developmental toxicity hinges on its control of intracellular ROS levels, involving the inhibition of Nrf2 and the upregulation of recombinant Keap1, a specific target of Nrf2 [16].…”
Section: Chelerythrine Induces Apoptosis and Ferroptosis Through Nrf2...mentioning
confidence: 99%
“…endoplasmic reticulum stress and subsequent apoptosis [15]. Furthermore, research in zebrafish has unveiled that CHE's developmental toxicity hinges on its control of intracellular ROS levels, involving the inhibition of Nrf2 and the upregulation of recombinant Keap1, a specific target of Nrf2 [16].…”
Section: Chelerythrine Induces Apoptosis and Ferroptosis Through Nrf2...mentioning
confidence: 99%
“…Moreover, the main mechanism of action is correlated with the alteration of phosphoinositide 3-kinase (PI3K), Akt, and the mammalian target of rapamycin (mTOR) signaling pathways [ 35 ]. Chelerythrine ( 2 ) has exhibited anticancer activity in vivo and in vitro, and considerable existing research has confirmed that chelerythrine can act on different pathways (e.g., DNA, MAPK, apoptosis, ROS, cell cycle, autophagy, tumor metastasis, and PKC) to inhibit or facilitate apoptosis in a variety of cancer cells (e.g., non-small cell lung cancer [ 36 ], prostate cancer [ 37 ], lung adenocarcinoma [ 38 ], renal cancer [ 39 ], and melanoma cells [ 40 ], colorectal cancer [ 41 ]), thus suggesting that the benzophenanthridine alkaloids exhibit high anticancer activity. Previous studies have proven that chelerythrine ( 2 ) exhibits antitumor stem cell properties, which are mediated by the downregulation of β- Catenin expression, thus inhibiting non-small cell lung cancer stem cells [ 42 ].…”
Section: Antitumor Activities Of Benzophenanthridine Alkaloids From N...mentioning
confidence: 99%
“…Which are not only similar in structure, but also similar in mechanism of action ( Liu et al, 2023 ). Both alkaloids have been proved to have antibacterial and anti-inflammatory activities, with the activity of sanguinarine being more prominent ( Hamoud et al, 2014 ; Kumar and Hazra, 2015 ; Xue et al, 2017 ; Kulíšková et al, 2023 ; Liang et al, 2023 ). Currently, the research on MCE is mainly focused on improving the growth performance of poultry, and there is no study on the mechanism of its regulation of meat quality.…”
Section: Introductionmentioning
confidence: 99%